The Role of the Cell Surface Mucin MUC1 as a Barrier to Infection and Regulator of Inflammation - Dhar, Poshmaal; McAuley, Julie (Frontiers in Cellular and Infection Microbiology, 2019)
The family of cell surface (cs-) mucins reside beneath the gel-mucin layer, being constitutively expressed at the cell surface by nearly all epithelial cells. All cs-mucin family members have structural features that provide a barrier function to mucosal pathogens by displaying sites for pathogen binding, acting as a releasable decoy and sterically blocking binding of pathogens to underlying cellular receptors. The cytoplasmic tail domain of cs-mucins is highly conserved across species and are capable of initiating signal transduction cascades. MUC1 is one of the most extensively studied of the cs-mucin family. With respect to its physiological function in the mucosal environment, MUC1 has been demonstrated to play a dynamic role in protection of the host from infection by a wide variety of pathogens and to regulate inflammatory response to infection. This review briefly summarizes the current knowledge and new findings regarding the structural features relating to the function of MUC1, its role as a protective barrier against pathogen invasion and mechanisms by which this cs-mucin regulates inflammation.